응용미술저작물의 저작권 보호 및 디자인보호법과의 조정 - 정연덕 (원광법학, 41(1), 2025)
미술저작물의 상업화가 증가하면서, 저작권법상 응용미술저작물의 범위가 확대되고 있다. 이로 인해 디자인보호법상의 디자인 개념과 경계가 모호해지며, 응용미술작품의 보호와 활용을 저작권법과 디자인보호법을 함께 고려하여 조정할 필요성이 커지고 있다. 순수미술과 응용미술의 구분이 희미해지면서 동일한 저작물이 상황에 따라 순수미술저작물 또는 응용미술저작물로 판단될 가능성이 커진다. 인공지능(AI) 기술이 발전하면서 생성형 AI가 디자인과 브랜드 등 다양한 영역과 결합하며 보호대상의 중첩 문제가 더욱 확대되고 있다. 디자인과 응용미술의 중복 보호는 현대 법체계에서 허용되는 추세이며, 이를 입법적으로 조정하는 것이 중요한 과제가 되었다. 디자인보호법은 물품성과 등록 절차를 요구하며 보호 기간이 상대적으로 짧지만, 저작권법은 무방식주의 원칙에 따라 자동 보호되며 보호 기간이 길다. 이에 따라 동일한 창작물이 두 법률의 적용을 받을 경우가 증가하고 있으며, 법적 경계가 모호해지고 있다. 특히, 최근 디지털 디자인의 중요성이 증가함에 따라 가상공간에서 활용되는 UI･UX, VR･AR 기반 디자인이 보호 공백에 놓일 가능성이 크다. 개정 디자인보호법이 화상디자인을 보호 대상으로 포함했으나, 기기의 조작과 기능 발휘에 한정되어 있어 메타버스 내 디지털 상품 보호에는 한계가 있다. 따라서, 디자인보호법의 물품성 요건을 완화하고, 저작권법과 연계하여 응용미술디자인 보호 범위를 확대하는 제도적 정비가 요구되며, 법적 불확실성을 줄이기 위한 명확한 기준이 필요하다. 응용미술저작물과 산업디자인 보호의 경계 문제를 해결하기 위한 법적 정비가 필요하다. 중복보호가 되고 있지만 상대적으로 저작권법에 의한 보호를 확대하는 것이 필요하다. 응용미술의 보호는 대량 생산 여부에 따라 차별적으로 접근해야 한다. 대량 생산되는 공업제품은 디자인의 자유 이용을 촉진하는 것이 중요하며, 저작권 보호를 제한할 필요가 있다. 반면, 양산이 어려운 응용미술의 경우 저작권 보호를 강화해야 한다. 응용미술의 경우 디자인보호법은 절차가 복잡하고 비용 부담이 크므로 저작권법을 선호하는 창작자가 많다. 이에 따라, 저작권법을 통한 보호 방식을 확대하고, 등록 절차 없이 자동으로 보호받을 수 있도록 하는 제도 개선이 필요하다. 특히, 가상 상품과 같은 디지털 디자인은 상업적 성격이 강하며, 물품성이 없어 디자인법으로 보호받기 어려우므로, 저작권법을 통한 보호가 필요하다. 또한, 디자인공지증명제도를 응용미술저작물에도 확대 적용하여 저작권법상 창작물의 권리를 사전에 입증할 수 있도록 해야 한다. 아울러, ‘가상융합산업 진흥법’의 임시기준 제도를 가상사계에서의 응용미술 보호에 도입하여, 선제적 규제보다는 사후적 규제를 적용함으로써 산업 발전을 저해하지 않는 유연한 보호 체계를 마련할 필요가 있다. As the commercialization of artistic works increases, the scope of applied artworks under copyright law is expanding. Consequently, the concept and boundaries of design under design protection law have become ambiguous, highlighting the need to coordinate the protection and utilization of applied artworks by considering both copyright law and design protection law. The distinction between fine art and applied art is becoming increasingly blurred, making it more likely that the same work may be classified as either fine art or applied art depending on the context. With the advancement of artificial intelligence (AI) technology, generative AI is integrating with various domains such as design and branding, further exacerbating issues of overlapping protection. In modern legal systems, the dual protection of design and applied art is becoming more common, making legislative coordination a critical issue. Design protection law requires materiality and registration procedures, offering a relatively short protection period, whereas copyright law follows the principle of non-formality, granting automatic protection with a longer duration. As a result, an increasing number of creative works fall under both legal frameworks, leading to legal ambiguities. In particular, as digital design gains prominence, UI/UX, VR, and AR-based designs used in virtual spaces are at risk of falling into a protection gap. Although the amended design protection law now includes screen designs as a subject of protection, its coverage is limited to designs related to device operation and functionality, making it insufficient for protecting digital products within the metaverse. Therefore, there is a need to relax the materiality requirement in design protection law and expand the protection scope of applied art designs in coordination with copyright law. Establishing clear legal standards is essential to reducing legal uncertainty and resolving boundary issues between applied artwork and industrial design protection. While dual protection exists, it is necessary to expand copyright-based protection. The protection of applied art should be approached differently depending on whether it is mass-produced. For industrial products that are manufactured in large quantities, prioritizing the free use of design is crucial, necessitating restrictions on copyright protection. Conversely, in cases where applied art is difficult to mass-produce, copyright protection should be strengthened. For applied artworks, many creators prefer copyright law over design protection law due to its complex procedures and high costs. Hence, expanding copyright-based protection and implementing a system where works are automatically protected without registration procedures is necessary. Digital designs, such as virtual goods, have a strong commercial nature but lack materiality, making them difficult to protect under design law. As such, they should be safeguarded under copyright law. Additionally, the design disclosure certification system should be extended to applied artworks, enabling the preemptive proof of rights under copyright law. Furthermore, incorporating the “Temporary Standards” system from the Act on the Promotion of Virtual Convergence Industry into the protection of applied art in virtual environments could provide a flexible regulatory framework. By applying ex-post regulation rather than preemptive regulation, it would ensure a legal structure that supports industrial growth without hindering innovation. KCI Citation Count: 0